Lung Adenocarcinoma Harboring EGFR Kinase Domain Duplication (EGFR-KDD) Confers Sensitivity to Osimertinib and Nivolumab: A Case Report - Li, Jie; Yan, Junrong; Cao, Ran; Du, Guanjun; Zhao, Guofang (Frontiers in Oncology, 2020)
Background: Kinase domain duplication of EGFR (EGFR-KDD) is a rare oncogenic driver alteration and serves as a potential therapeutic target. Its effect on EGFR-tyrosine kinase inhibitors (TKIs), especially the third-generation drug Osimertinib, and immune checkpoint inhibitors (ICIs) remains inconclusive. Case Presentation: A 45-year old male with lung adenocarcinoma progressed with liver metastasis after receiving pemetrexed and cisplatin as adjuvant chemotherapy. Targeted next-generation sequencing (NGS) identified an EGFR-KDD in the resected left upper lung. Icotinib was used in the following treatment and the liver metastasis was found to shrink but the progression free survival (PFS) only lasted for 4 months with the appearance of right hepatic metastasis. Meantime, the same EGFR-KDD was identified in the left hepatic re-biopsy. Afterwards, the patient benefited from the third-line therapy of Osimertinib with a PFS as long as 21 months. Then he progressed with enlarged mediastinal lymph nodes, and targeted NGS consistently identified EGFR-KDD, as well as a new RELN p.G1774E mutation. Given the continually increasing tumor mutation burden (TMB, 3.4 mutation/Mb) and PD-L1 expression-based tumor proportion score (TPS, 1%), Nivolumab was used as the fourth-line salvage therapy, which lead to considerable efficacy, with decreased blood carcinoembryonic antigen (CEA), regressed mediastinal lymph nodes, and reduced liver metastases. Conclusions: Our case provided direct evidence to support the role of Osimertinib in the treatment of EGFR-KDD, as well as added valuable insights into application of immune-based therapeutics in the specific subgroups bearing EGFR alteration(s).